9b-7b+6=-4b+78-3b

Simple and best practice solution for 9b-7b+6=-4b+78-3b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9b-7b+6=-4b+78-3b equation:


Simplifying
9b + -7b + 6 = -4b + 78 + -3b

Reorder the terms:
6 + 9b + -7b = -4b + 78 + -3b

Combine like terms: 9b + -7b = 2b
6 + 2b = -4b + 78 + -3b

Reorder the terms:
6 + 2b = 78 + -4b + -3b

Combine like terms: -4b + -3b = -7b
6 + 2b = 78 + -7b

Solving
6 + 2b = 78 + -7b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '7b' to each side of the equation.
6 + 2b + 7b = 78 + -7b + 7b

Combine like terms: 2b + 7b = 9b
6 + 9b = 78 + -7b + 7b

Combine like terms: -7b + 7b = 0
6 + 9b = 78 + 0
6 + 9b = 78

Add '-6' to each side of the equation.
6 + -6 + 9b = 78 + -6

Combine like terms: 6 + -6 = 0
0 + 9b = 78 + -6
9b = 78 + -6

Combine like terms: 78 + -6 = 72
9b = 72

Divide each side by '9'.
b = 8

Simplifying
b = 8

See similar equations:

| 11x-160=56-7x | | 10+58=6x+2 | | 2x^4+3x-50=0 | | 5a+4b-5(7a-9b)= | | 26w+20=956 | | X-2x=125 | | (1+y)x^2-3yx+(1-y)=0 | | 2.50(m+15.00)=412.5 | | 84=2x-4+2x+4 | | 75=4529 | | -1-10r^2=-881 | | 3.4=y+2.1 | | -3x^2+8x-6=0 | | -8p-8=-14-7p | | -2x+(-21)=23 | | -1-10r^2=881 | | 84=4x^2-8+8-16 | | 929=97+13r | | 31/2(6x-21/2)+51/3=-62/3(-3x+16/5)+122/3 | | -70=-2(n+5)+7(4-6n) | | 21m-9= | | 15(b+17)=555 | | 7(f+37)=693 | | -147=-5x-4(-5x+18) | | 10x-1=35+x | | 200=2z | | -23(u-946)=-322 | | 2m^2+9=41 | | x+(x-40)=92 | | 4x-205-x=230 | | 8-5(4-3z)=2(4-2)8z | | 5.28x+31.68=63.36 |

Equations solver categories